Comparative efficacy study of combination fansidar-sulphate-quinine and fansidar-hcl-tetracycline in falciparum malaria in children above 7 years old - K. Silitonga; T. H. Rampengan (Paediatrica Indonesiana, 1991)
The objective of this study is to compare the results of treatment of children with falciparum malaria with the combinations of fansidar-su/phate quinine and fansidar-chlortetracycline as an alternative treatment of chloroquine'resistant falciparum malaria. This study was carried out prospectively on 45 cases with the age equal or above 7 years, who had been admitted in the Pediatric Department, Gunung Wenang Hospital, Manado, during the period of January 1989- December 1989. Twenty three cases had been treated with fansidar - sulphate quinine and 22 cases with fansidar-chlortetracycline, all of them underwent blood examinations for malaria for 7 consecutive days (day 0-8). Asexual parasitemia and fever in the fansidar-sulphate quinine group significantly disappeared more rapidly than in the fansidar-chlortetracycline group (P <0.03 and <0.005). There occurred neither drug resistance nor serious side effect in both groups.